The intensification of anticancer activity of LFM-A13 by erythropoietin as a possible option for inhibition of breast cancer. (1st January 2020) - Rozkiewicz, Dariusz; Hermanowicz, Justyna Magdalena; Tankiewicz-Kwedlo, Anna; Sieklucka, Beata; Pawlak, Krystyna; Czarnomysy, Robert; Bielawski, Krzysztof; Surazynski, Arkadiusz; Kalafut, Joanna; Przybyszewska, Alicja; Koda, Mariusz; Jakubowska, Katarzyna; et al.
Abstract: Recombinant human erythropoietin (Epo) is an effective and convenient treatment for cancer-related anaemia. In our study for the first time, we evaluated the effect of simultaneous use of Epo and Bruton's tyrosine kinase (BTK) inhibitor LFM-A13 on the viability and tumour development of breast cancer cells. The results demonstrated that Epo significantly intensifies the anticancer activity of LFM-A13 in MCF-7 and MDA-MB-231. The featured therapeutic scheme efficiently blocked the tumour development in zebrafish experimental cancer model. Epo and LFM-A13 administered together resulted in effective cell killing, accompanied by attenuation of the BTK signalling pathways, loss of mitochondrial membrane potential (MMP), accumulation of apoptotic breast cancer cells with externalised PS, a slight increase in phase G0/G1 and a reduction in cyclin D1 expression. Simultaneous use of Epo with LFM-A13 inhibited early stages of tumour progression. This therapeutic scheme may be rationale for further possible research.